Flexible Drafting and its impact on Abstraction in the penalty rule - Ali, Alyaa; Dahash, Qaid (Journal of Legal Sciences, 2023)
This study seeks to define the idea of ​​abstraction in the rules of criminalization and punishment and to indicate the extent of privacy that it enjoys in the field of criminalization and punishment, which is represented in the fact that it is not absolute as in the general legal rule, but rather it is restricted by several restrictions, which are due to the nature of this law and the basic functions it performs in society and the nature of The penalties it contains and its aim, which is represented in achieving public deterrence, private deterrence, and justice. This study also explains the importance of abstraction in the rules of criminalization and punishment, represented in achieving justice and equality among all individuals, and achieving criminal legal certainty, in addition to the important practical functions that abstraction performs, whether when setting the law. by the legislator or when applying it. And This study shows the most important restrictions on abstraction in the penal rule, which is represented in the flexible formulation of these texts in flexible and stretchy phrases that the judge, when applied, can include facts in the punitive text, because they are not defined, which contradicts the abstraction feature in the criminalization and penalty rules, which are required to Criminal acts are determined according to an abstract criminal model established by the legislator, in which it is required that it be specific, disciplined, and clear so that individuals know the behavior that they are prohibited from committing And identifying the cases in which the flexible wording of criminalization texts is a restriction on abstraction in the rules of criminalization and punishment, whose purpose is to make these rules more just and keep pace with the various changes, and the cases in which the flexible wording is a means to achieve private interests.